Pengaruh interaksi lingkungan keluarga terhadap pemerolehan bahasa pada anak usia 3-4 Tahun - Rahmawati, Silvia Dewi; Ramdhan, Ramdhan Adi Wibowo; Dona, Dona Aji (Universitas Lampung, 2024)
The purpose of this study was to describe the language acquisition of children aged 3 years 10 months in terms of phonology, morphology, and syntax. This study was conducted using a descriptive qualitative method. The subject in this study was a 3 year 10 Month old girl with the initials Cila. The data in the study were in the form of speech produced by Cila which was collected using documentation, listening, and note-taking techniques. The findings of this study indicate that: 1) At the phonology level, the subject has mastered vowels well. While in the acquisition of consonants, there is one phoneme that is still difficult to pronounce, namely the phoneme /ŋ/. 2) At the morphology level, the vocabulary mastered by the subject is quite broad, including monomorphemic words and bound morpheme forms. 3) At the syntax level, the subject has been able to form good sentence patterns so that it produces complex sentences, including four types of sentences, namely imperative sentences, interrogative sentences, declarative sentences, and complex sentences.Keywords: Language Acquisition; Children Aged 3-4 Years; Phonology; Morphology, Syntax